Ipidacrine efficacy in diabetic polyneuropathy complex treatment: A review - Olga E. Zinovyeva; Pavel D. Egorov; Anna I. Penkina; Samir S. Guseinov (ZAO "Consilium Medicum", 2022)
Diabetic polyneuropathy (DPN) is a common neurological complication of diabetes mellitus. The most common DPN type is distal symmetric, predominantly sensory, polyneuropathy (DSPN), often accompanied by pain syndrome. This article is aimed to evaluate of ipidacrine (Ipigrix) efficacy in complex DSPN therapy. The dynamics of clinical and neurophysiological manifestations of DPN in the form of the appearance of previously absent tendon reflexes, a decrease in the area and severity of sensory disturbances, the intensity of neuropathic pain, an increase in the amplitude of motor and sensory responses in response to stimulation of peripheral nerves indicates the activation of reinnervation processes against the background of therapy using ipidacrine. Assessing the positive effect on the restoration of the structure and function of peripheral nerves, good tolerability and safety of ipidacrine (Ipigrix), it is possible to recommend the drug in patients with DSPN.